The Influence of Facilities and Price on User Satisfaction with Rukita Brand Awareness as a Moderator - Soetiyani, Ari; Nathadiharja, Sri Sukartono; Muharomi, Sri (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study, titled "The Influence of Facilities and Rental Price of Rukita Boarding Houses on User Satisfaction with Brand Awareness as a Moderating Variable," was conducted in response to the growing competition within the property industry, particularly in the modern boarding house segment. It examines four variables: user satisfaction as the dependent variable, facilities and rental price as independent variables, and brand awareness as a moderating variable. The study aims to determine whether facilities and rental prices significantly affect user satisfaction and whether brand awareness strengthens these relationships. Using a causal research design and Structural Equation Modeling (SEM) with SmartPLS, the findings reveal that both facilities and rental price significantly influence user satisfaction. Moreover, brand awareness has a direct positive effect on satisfaction and moderates the relationship between facilities and satisfaction, though it does not moderate the relationship between price and satisfaction. These results suggest that brand awareness enhances perceptions of facility quality but does not reduce user sensitivity to price. The study offers valuable insights for Rukita and similar businesses to improve facility quality and consistently build brand awareness, while maintaining rational pricing strategies to ensure customer satisfaction in a competitive market.